2016
DOI: 10.3389/fphys.2016.00509
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammatory Cytokines and BDNF Response to High-Intensity Intermittent Exercise: Effect the Exercise Volume

Abstract: The purpose of this study was to compare the effects of two similar high-intensity intermittent exercises (HIIE) but different volume 1.25 km (HIIE1.25) and 2.5 km (HIIE2.5) on inflammatory and BDNF responses. Ten physically active male subjects (age 25.22 ± 1.74 years, body mass 78.98 ± 7.31 kg, height 1.78 ± 0.06 m, VO2peak 59.94 ± 9.38 ml·kg·min−1) performed an incremental treadmill exercise test and randomly completed two sessions of HIIE on a treadmill (1:1 min at vVO2max with passive recovery). Blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 37 publications
7
61
0
Order By: Relevance
“…Regardless of, levels of IL‐10 tend to peak at the cessation of the exercise or shortly thereafter. One previous study shows that after acute exercise (5‐km continuous run on a treadmill at 70% of sVO 2 max) peak concentrations of IL‐10 were reached 60 min after the cessation of acute exercise compared with baseline levels (Cabral‐Santos et al, ). Thus, the systemic effects induced by IL‐10 are for the most part perceived to occur during recovery time from exercise.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regardless of, levels of IL‐10 tend to peak at the cessation of the exercise or shortly thereafter. One previous study shows that after acute exercise (5‐km continuous run on a treadmill at 70% of sVO 2 max) peak concentrations of IL‐10 were reached 60 min after the cessation of acute exercise compared with baseline levels (Cabral‐Santos et al, ). Thus, the systemic effects induced by IL‐10 are for the most part perceived to occur during recovery time from exercise.…”
Section: Discussionmentioning
confidence: 96%
“…In response to amount of time, prior research has showed that in high‐intensity intermittent exercises of different exercise volumes (running 1.25 and 2.5 km with 1:1 min at sVO 2 max) the increase in IL‐10 concentration was related to the duration of exercise indicating the importance of this variable (Cabral‐Santos et al, ). Taken together, these results showed that changes in IL‐10 production are remarkably related to the duration of exercise.…”
Section: Discussionmentioning
confidence: 98%
“…It should be highlighted that contracting muscles secrete IL‐6, stimulating the appearance in the circulation of the anti‐inflammatory cytokine IL‐10, which directly inhibits TNF‐α transcription . However, IL‐10 release into the circulation is not a consistent finding in response to high‐intensity exercise protocols . Our results suggest that “all out” sprint exercise is a good time‐efficient strategy for promoting an anti‐inflammatory response.…”
Section: Discussionmentioning
confidence: 68%
“…11 However, IL-10 release into the circulation is not a consistent finding in response to high-intensity exercise protocols. 14,27,28 Our results suggest that "all out" sprint exercise is a good time-efficient strategy for promoting an anti-inflammatory response.…”
Section: Inflammatory Response To Sprint Interval Trainingmentioning
confidence: 71%
“…A lot of research was performed on the kinetics of changes in cytokine levels following acute exercise [ 44 , 46 , 47 ] and regular physical activity [ 48 , 49 ]. The effects of gender [ 46 ], training loads [ 50 ], and age [ 48 , 49 ] on the kinetics of posttraining cytokine levels were also analyzed.…”
Section: Discussionmentioning
confidence: 99%